USE OF DIETARY SUPPLEMENTS FOR WEIGHT LOSS IN OBESE PATIENTS IN ZONGULDAK, TURKEY - Erdogan, Zeynep; Kurtuncu, Meltem (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Obesity is a prevalent and worldwide health problem . The most common weight loss method preferred by obese individuals is dietary supplements. This study was performed in order to determine the dietary supplements used by obese individuals for weight loss and to examine the barriers to informing health personnel on supplement use.Materials and Methods: This descriptive study was performed in the Endocrinology and Diabetes Polyclinic at the Endocrinology and Metabolic Diseases Department of the Health Application and Research Center of the Bulent Ecevit University. The sample consisted of 151 patients randomly selected from among the 755 people using the simple randomization method.Results: In the study, 33.6% of the obese individuals were found to use dietary supplements for weight loss. Women, people with no chronic diseases, people who exercised regularly, and people who underwent regular health check-ups were found to prefer dietary supplements at a greater rate (p<0.05). It was found that 82.5% of the obese individuals used dietary supplements without informing health personnel.Conclusion: One thirds of obese individuals were using dietary supplements for weight loss, while the majority of supplement users did not inform health personnel. To increase patient safety, the patients using dietary supplements should be closely monitored, and the use of dietary supplements should be evaluated on a routine basis.